(NsILXWANDIR(B: [(NrOMAN(B] / s - (Nd@MA(B, (NaLEKSANDRs ((NsANKT(B-(NpETERBURG(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1992)
(NzAWQZKA \TOGO ROMANA a(B. (Nd@MA (B(1802-1870) (NNAPOMINAET NA^ALXNYE GLAWY (B"(NtREH MU[KETEROW(B", (NPEREVIWANIQ I RAZMY[LENIQ GLAWNOGO GEROQ rOVE tANKREDA W T@RXME WYZYWA@T W PAMQTI TERZANIQ |DMONA dANTESA (B("(NgRAF mONTE(B-(NkRISTO(B"). (Nw CELOM VE \TO PROIZWEDENIE(B, (NOTLI^A@]EESQ PROSTOTOJ I IZQ]ESTWOM I ZASLUVIW[EE ODOBRITELXNU@ OCENKU l(B. (Nn(B. (NtOLSTOGO(B, (NPOWESTWUET O L@BWI(B, (NWERNOSTI I ^ESTI(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NpRIKL@^EN^ESKIJ ROMANs